Sleep and cardiorespiratory function assessed by a smart bed over 10 weeks post COVID-19 infection - Gary Garcia-Molina; Dmytro Guzenko; Susan DeFranco; Mark S. Aloia; Rajasi Mills; Faisal Mushtaq; Virend K. Somers; Eve Van Cauter (Scientific Reports)
Abstract Inadequate information exists regarding physiological changes post-COVID-19 infection. We used smart beds to record biometric data following COVID-19 infection in nonhospitalized patients. Recordings of daily biometric signals over 14 weeks in 59 COVID-positive participants’ homes in 2020 were compared with the same participants’ data from 2019. Participants completed a survey of demographic information, health conditions, COVID exposure and testing, and symptom prevalence/subjective severity. Mean age was 47.5 years (standard deviation [SD] 9.5), mean body mass index was 30.1 kg/m2 (SD 7.1), and 46% were men. During acute infection, 64% exhibited 5–6 h increased sleep duration, 51% had increased movement, and 64% had increased breathing rate (BR). Nearly 34% had paradoxical bradycardia (decreased heart rate by ~ 10 BPM concomitant with elevated BR and/or fever), with more-severe symptoms. Smart beds can detect physiological changes during COVID-19. A subtype of acute response (paradoxical bradycardia) may predict delay recovery from COVID-19.